ENSURING CYBERSECURITY IN BANKING CARDS: GLOBAL RISK TRANSFORMATION AND FOREIGN MODELS - Mokhichehra Kurbonbekova; Guzal Mamadiyarova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
This article examines the issue of ensuring cybersecurity in banking card systems from the perspective of global risk transformation. In the context of the digital economy, payment infrastructure is evolving into not only a technological domain but also a strategic risk center. Drawing on the models of the United States, the European Union, Singapore, and Japan, the study explores cyber risk management architecture, institutional coordination, proactive monitoring systems, and the concept of digital trust. The paper proposes an integrated model for ensuring banking card security based on the formula “technology + regulation + risk analytics + human capital.” cybersecurity, banking card security, digital payment systems, EMV technology, Strong Customer Authentication (SCA), fraud monitoring, artificial intelligence, risk management, skimming.